Selective research funding policy and catching up the ladder in university research performance in Malaysia. (29th October 2020) - Chandran, V.G.R.; Nourani, Mohammad; Selvarajan, Sonia Kumari; Baskaran, Angathevar
Abstract : This paper examines the post selective policy consequences on the university research performance, specifically between research universities (RUs) and non‐research universities (non‐RUs). The evidence shows significant achievement in scientific publications and patenting activities, due to additional funding allocation. Nevertheless, the overall efficiency performance is still low because of lack of efficiency in innovation efficiency and, starting 2010, in value creation efficiency. Non‐RUs are catching up in efficiency gains and have greater efficiency on value creation. This suggests that non‐RUs have concentrated on the revenue generation whereas RUs have picked the easier target, research publications and patenting activities, to justify funding.